Neuropathy following spinal nerve injury shares features with the irritable nociceptor phenotype: A back‐translational study of oxcarbazepine. (28th August 2018) - Patel, Ryan; Kucharczyk, Mateusz; Montagut‐Bordas, Carlota; Lockwood, Stevie; Dickenson, Anthony H.
Abstract: Background: The term 'irritable nociceptor' was coined to describe neuropathic patients characterized by evoked hypersensitivity and preservation of primary afferent fibres. Oxcarbazepine is largely ineffectual in an overall patient population, but has clear efficacy in a subgroup with the irritable nociceptor profile. We examine whether neuropathy in rats induced by spinal nerve injury shares overlapping pharmacological sensitivity with the irritable nociceptor phenotype using drugs that target sodium channels. Methods: In vivo electrophysiology was performed in anaesthetized spinal nerve ligated (SNL) and sham‐operated rats to record from wide dynamic range (WDR) neurones in the ventral posterolateral thalamus (VPL) and dorsal horn. Results: In neuropathic rats, spontaneous activity in the VPL was substantially attenuated by spinal lidocaine, an effect that was absent in sham rats. The former measure was in part dependent on ongoing peripheral activity as intraplantar lidocaine also reduced aberrant spontaneous thalamic firing. Systemic oxcarbazepine had no effect on wind‐up of dorsal horn neurones in sham and SNL rats. However, in SNL rats, oxcarbazepine markedly inhibited punctate mechanical‐, dynamic brush‐ and cold‐evoked neuronal responses in the VPL and dorsal horn, with minimal effects on heat‐evoked responses. In addition, oxcarbazepine inhibited spontaneous activity in the VPL. Intraplantar injection of the active metabolite licarbazepine replicated the effects of systemic oxcarbazepine, supporting a peripheral locus of action. Conclusions: We provide evidence that ongoing activity in primary afferent fibres drives spontaneous thalamic firing after spinal nerve injury and that oxcarbazepine through a peripheral mechanism exhibits modality‐selective inhibitory effects on sensory neuronal processing. Significance: The inhibitory effects of lidocaine and oxcarbazepine in this rat model of neuropathy resemble the clinical observations in the irritable nociceptor patient subgroup and support a mechanism‐based rationale for bench‐to‐bedside translation when screening novel drugs.